(untitled) (Applied Biological Research, 2015)
The present study was conducted on 100 cases of bovine calf diarrhea to monitor the activities of some serum enzymes viz., AST, ALP, GGT, CK and urea nitrogen in neonatal calves of different age groups. These calves were divided into 5 age groups viz., 1-7 day (7 calves), 8-14 days (5 calves), 15-21 days (30 calves), 22-30 days (19 calves) and 31-60 days (39 calves). The results of experimental groups were compared with normal standard values of different age groups. The diseased calves of all the age groups had significantly higher (p<0.01) serum AST activities as well as urea nitrogen as compared to control. Serum ALP activities were significantly low (p<0.01) in diseased calves of 8-14 days, 15-21 days and 31-60 days age groups. Alterations in other parameters were significant in specific age groups only.